Helicobacter pylori induce neutrophil transendothelial migration: Role of the bacterial HP-NAP - Brisslert, Mikael; Enarsson, Karin; Lundin, Samuel; Karlsson, Anna; Kusters, Johannes G.; Svennerholm, Ann-Mari; Backert, Steffen; Quiding-Järbrink, Marianne (FEMS microbiology letters, 2005)
Continuous recruitment of neutrophils into the inflamed gastric mucosal tissue is a hallmark of Helicobacter pylori infection in humans. In this study, we examined the ability of H. pylori to induce transendothelial migration of neutrophils using a transwell system consisting of a cultured monolayer of human endothelial cells as barrier between two chambers. We showed for the first time that live H. pylori, but not formalin-killed bacteria, induced a significantly increased transendothelial migration of neutrophils. H. pylori conditioned culture medium also induced significantly increased transendothelial migration, whereas heat-inactivated culture filtrates had no effect, suggesting that the chemotactic factor was proteinaceous. Depletion of H. pylori-neutrophil activating protein (HP-NAP) from the culture filtrates resulted in significant reduction of the transmigration. Culture filtrates from isogenic HP-NAP deficient mutant bacteria also induced significantly less neutrophil migration than culture filtrates obtained from wild-type bacteria. HP-NAP did not induce endothelial cell activation, suggesting that HP-NAP acts directly on the neutrophils. In conclusion, our results demonstrate that secreted HP-NAP is one of the factors resulting in H. pylori induced neutrophil transendothelial migration. We propose that HP-NAP contributes to the continuous recruitment of neutrophils to the gastric mucosa of H. pylori infected individuals.